Research progress on plant-derived natural compounds regulating the MAPK signaling pathway for the prevention and therapy of Alzheimer’s disease - Zhang, Xinyue; Huang, Shujia; Xu, Hongfeng; Hu, Yanan; Gao, Ling (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder. It is characterised by the following: amyloid-β (Aβ) deposition, tau hyperphosphorylation, neuroinflammation and oxidative stress. Unfortunately, there is no curative treatment available. Recently, natural products have attracted growing interest as potential therapeutic agents for AD, thanks to their multi-target actions and favourable safety profiles. This review highlights recent advances in the use of various natural compounds, including flavonoids, phenolic compounds, saponins, terpenoids, alkaloids and coumarins, with a particular focus on how they modulate the mitogen-activated protein kinase (MAPK) signaling pathway. Representative agents such as myricetin, nobiletin, resveratrol, gallic acid, paeoniflorin, ganoderic acid A, huperzine A, triptolide, berberine, crocin, and ginsenosides have been shown to regulate MAPK subpathways (ERK, JNK, p38), thereby attenuating oxidative stress, neuroinflammation, synaptic dysfunction, and neuronal apoptosis. Preclinical studies suggest that these compounds improve cognitive function and ameliorate AD-related pathology, thereby supporting the idea that MAPK signaling is a critical therapeutic target. Nevertheless, current evidence is limited by short-term animal experiments, insufficient toxicological evaluations, and challenges related to bioavailability and blood–brain barrier penetration. Future studies should emphasize long-term efficacy, safety assessments, optimized drug delivery systems, and high-quality clinical trials. Overall, natural products represent a valuable source for AD drug discovery, and targeting MAPK signaling offers promising opportunities for novel therapeutic development.